Nurse Managers' Experience in Managing Patient Screening at RSUP H. Adam Malik's Emergency Department During the COVID-19 Pandemic - Syahferi Anwar; Lutfi Henderlan Harahap; Balqis Nurmauli Damanik (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Nurse managers play an essential role in coordinating emergency department functions, especially during global health crises such as the COVID-19 pandemic. In low- and middle-income countries (LMICs), including Indonesia, their experiences have not been widely explored, despite facing unique logistical, emotional, and cultural challenges. This study aims to explore the lived experiences of nurse managers in overseeing COVID-19 screening procedures in the emergency department of RSUP H. Adam Malik Hospital in Medan, Indonesia. A descriptive phenomenological approach was employed to capture the essence of their experiences. Ten nurse managers were selected using purposive sampling. Data were collected through semi-structured interviews lasting 30 to 60 minutes, supplemented by field notes and document analysis. Colaizzi's seven-step method guided the analysis, with credibility ensured via member checking and triangulation using multiple informants. The study identified five major themes: (1) psychological distress in the early phase of the pandemic, stemming from fear, uncertainty, and concern for family safety; (2) challenges in implementing screening, including patient resistance, resource limitations, and PPE shortages; (3) proactive efforts for early COVID-19 detection through triage protocols and symptom-checking tools; (4) improvements in screening management, emphasizing leadership, education, and compliance; and (5) adaptation and resilience, as nurse managers developed strategies to cope with evolving demands and pressures. These themes reveal both universal healthcare struggles and context-specific issues-such as anxiety about infecting multigenerational households-that shaped nurse managers' responses. This research contributes to the limited body of qualitative evidence on pandemic leadership in LMICs. The insights gained underscore the importance of robust emergency preparedness, targeted psychological support for healthcare leaders, and ongoing improvements in screening protocols. Strengthening these areas can better equip healthcare systems to face future public health emergencies. Keywords: Nurse Managers, COVID-19, Emergency Department, Screening, Indonesia, LMICs.